Modern Urban Diasporas: Factors of Social Dynamics (on Materials of Tuva Diaspora in the City Of Abakan) - Marat N. Chistanov (Transbaikal State University, 2021)
In the summer and autumn of 2021, the Department of Philosophy and Cultural Studies of Khakass State University conducted a pilot sociological study of the Tuvan diaspora in the city of Abakan. One of the main tasks of the study was to build a general integrated theoretical model of the identity of ethnic communities, which would be applicable to the analysis of ethnocultural processes in modern urban conditions. Diasporas are seen as complex multilevel systems that can be visualized through a set of specific behavioral scenarios. These scenarios were supposed to be investigated using the methodology of the frames of Ervin Goffman and the concept of iconic turn in the culture of Ilya Inishev. The preliminary results of the study are presented in this article. It is argued that modern ethnic diasporas have a second or third-order ethnic identity (arising after the traditional and industrial stages of social development). This identity is characteristic of adults who have passed through people who have created a family, have children, an education and a profession, but for various reasons they have not realized themselves in their historical homeland. Ethnic identity of such people does not involve participation in ethnic organizations and associations, but involves the use of visual markers that signal their own ethnic identification and self-identification. In the first approach, the model seems justified, the materials of the in-depth interviews and the expert interviews as a whole correspond to its basic provisions. Further development and adjustment of the model will be possible after processing of all empirical data and analysis of the study results.